Host plant mediates foraging behavior and mutual interference among adult Stethorus gilvifrons (Coleoptera: Coccinellidae) preying on Tetranychus urticae - Bayoumy, Mohamed H.; Osman, Mohamed A.; Michaud, J. P. (My University, 2014)
Physical plant characteristics can influence predator foraging and their behavioral responses to each other. This study examined the searching efficiency and functional response of adult female Stethorus gilvifrons Mulsant foraging for Tetranychus urticae Koch (Acari: Tetranychidae) on castor bean, common bean, and cucumber leaves. Experiments conducted on leaf discs in arenas for 12 h revealed a type II functional response for S. gilvifrons on all host plants. Per capita searching efficiency and killing power decreased with increasing predator density on all plants, but most notably on common bean, the plant with the highest prey consumption rates, due to greater mutual interference. Attack rates were highest on common bean and lowest on castor bean, whereas handling times were shortest on common bean and longest on cucumber, such that the daily predation rate was maximal on common bean. Host plant interacted with predator and prey densities to affect searching efficiency and functional response, the differences in mite consumption among host plants increasing with predator and prey densities. The waxy layers of castor bean leaves and high trichome counts of cucumber leaves appeared to reduce predator foraging efficiency. Thus, the efficacy of S. gilvifrons against T. urticae is likely to be greatest on plants such as Phaeseolus vulgaris L. that have relatively smooth leaves.
Host plant mediates foraging behavior and mutual interference among adult Stethorus gilvifrons (Coleoptera: Coccinellidae) preying on Tetranychus urticae (Acari: Tetranychidae)
Citation: Bayoumy, M. H., Osman, M. A., & Michaud, J. P. (2014). Host plant mediates foraging behavior and mutual interference among adult Stethorus gilvifrons (Coleoptera: Coccinellidae) preying on Tetranychus urticae. Retrieved from http://krex.ksu.edu
Keywords: Area of discovery; Attack rate; Density-dependence; Functional response; Handling time